7(x-3)-(9x+2)=15

Simple and best practice solution for 7(x-3)-(9x+2)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-3)-(9x+2)=15 equation:


Simplifying
7(x + -3) + -1(9x + 2) = 15

Reorder the terms:
7(-3 + x) + -1(9x + 2) = 15
(-3 * 7 + x * 7) + -1(9x + 2) = 15
(-21 + 7x) + -1(9x + 2) = 15

Reorder the terms:
-21 + 7x + -1(2 + 9x) = 15
-21 + 7x + (2 * -1 + 9x * -1) = 15
-21 + 7x + (-2 + -9x) = 15

Reorder the terms:
-21 + -2 + 7x + -9x = 15

Combine like terms: -21 + -2 = -23
-23 + 7x + -9x = 15

Combine like terms: 7x + -9x = -2x
-23 + -2x = 15

Solving
-23 + -2x = 15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '23' to each side of the equation.
-23 + 23 + -2x = 15 + 23

Combine like terms: -23 + 23 = 0
0 + -2x = 15 + 23
-2x = 15 + 23

Combine like terms: 15 + 23 = 38
-2x = 38

Divide each side by '-2'.
x = -19

Simplifying
x = -19

See similar equations:

| 10x-5(3x+5)=-10x | | 37-17=4(x-9) | | x^2+18x+75=-6 | | 7x=52 | | -2.1=d+(-9.3) | | 75+4v=150+1v | | 6(x-6)-10= | | a(b-2)=3a+b(a)-5a | | x^2+13=9x-5 | | 21+8y+10m-5y-5m+10= | | 2(2x-5)=54 | | 0=24-12x | | h/1.05=-0.36 | | 6d=144 | | x-2x+2=-1 | | w+5.3=-10.1 | | 14x+9=30-x | | 13j-100=7j-680 | | x^2+11=10x-5 | | .25(12-8x)=4(-2x-6) | | x-4+9=0 | | 15=4q+3 | | x^2-4x=-2x+63 | | -4.5+12.3=-23.7 | | 9(v-89)=27 | | x+2x-4=-13 | | 3+5c=-12 | | x+2x-4=13 | | 24=100 | | 11-11+3x=38-11 | | Y^3-8y^2-9y+72=0 | | x^2+150x-5000=0 |

Equations solver categories